Reflections on Democratic Deliberation in Bioethics - Gutmann, Amy (The Hastings Center report, 2017)
Over the course of six years and more than two dozen meetings, members of the Presidential Commission for the Study of Bioethical Issues learned so many things: about emerging science; technological challenges; citizen engagement; the public's, experts’, and our own understandings and misperceptions; and even the nature of our own most cherished values. Our commission's commitment to democratic deliberation began deliberatively, when we decided (in the summer of 2010) upon basic principles to guide our first report. At the time, Craig Venter had just announced that he had used techniques of synthetic biology to “create life,” albeit the most elementary form of life, from nonliving building blocks. Headlines alternated between applauding Venter for creating life and accusing him of playing God. It was one of those all-too-frequent instances where sound-bite democracy was headed toward shedding more heat and fear than light and understanding. The commission was asked to take synthetic biology under review and make recommendations to President Obama on how to proceed. We saw the need to question the most salient facts of the matter: what were the fundamental values at stake in this kind of discovery?